Aspirin inhibits osteoclast formation and wear‐debris‐induced bone destruction by suppressing mitogen‐activated protein kinases. Issue 3 (9th September 2019) - Shi, Jiawei; Wang, Zhen; Guo, Xiaobin; Shen, Jining; Sun, Houyi; Bai, Jiaxiang; Yu, Binqing; Wang, Liangliang; Zhou, Wei; Liu, Yu; Zhang, Wen; Yang, Huilin; et al.
Abstract: Excessive osteoclast recruitment and activation is the chief cause of periprosthetic osteolysis and subsequent aseptic loosening, so blocking osteolysis may be useful for protecting against osteoclastic bone resorption. We studied the effect of aspirin on titanium (Ti)‐particle‐induced osteolysis in vivo and in vitro using male C57BL/6J mice randomized to sham (sham surgery), Ti (Ti particles), low‐dose aspirin (Ti/5 mg·kg −1 ·d −1 aspirin), and high‐dose aspirin (Ti/30 mg·kg −1 ·d −1 aspirin). After 2 weeks, a three‐dimensional reconstruction evaluation using micro‐computed tomography and histomorphology assessment were performed on murine calvariae. Murine hematopoietic macrophages and RAW264.7 lineage cells were studied to investigate osteoclast formation and function. Aspirin attenuated Ti‐particle‐induced bone erosion and reduced osteoclasts. In vitro, aspirin suppressed osteoclast formation, osteoclastic‐related gene expression, and osteoclastic bone erosion in a dose‐dependent manner. Mechanically, aspirin reduced osteoclast formation by suppressing receptor activator of nuclear factor kappa‐B ligand‐induced activation of extracellular signal‐related kinase, p‐38 mitogen‐activated protein kinase, and c‐Jun N‐terminal kinase. Thus, aspirin may be a promising option for preventing and curing osteoclastic bone destruction, including peri‐implant osteolysis. Abstract : Aspirin blocks receptor activator of nuclear factor kappa‐B ligand‐induced mitogen‐activated protein kinase activation and osteoclast formation, and subsequently attenuates wear‐debris‐induced osteolysis. Thus, aspirin might be an appropriate reagent for treating osteoclastic bone loss, including peri‐implant osteolysis.